O-170 Predictive value of cytoplasmic granulation patterns during IVF in MII oocytes from young donors. (6th August 2021) - Hu, J; Molinari, E; Darmon, S; Albertini, D F; Barad, D H; Gleicher, N
Abstract: Study question: Do ooplasm granulation patterns of donor MII oocytes have similar predictive values for in vitro fertilization (IVF) outcomes as they have in older infertile women? Summary answer: Ooplasm granulation patterns of donor MII oocytes are predictive for IVF outcomes in young oocyte donors even more pronounced than in older poor prognosis patients. What is known already: Cytoplasmic granules had been noticed for years, with data mostly focused on central granulation. Dispersed granulations were mentioned but lacked analysis. Study design, size, duration: A retrospective cohort study during 2017-2020. Participants/materials, setting, methods: We investigated 776 fresh and 381 vitrified-thawed MII oocytes from carefully selected young donors (mean, 26.7±2.7; range, 21-35 years) and determined cytoplasmic granulation patterns during intracytoplasmic sperm injection as fine, central, uneven, dispersed and peripheral (see only in thawed oocytes). Fertilization, pregnancy and live-birth rates in fresh and thawed donor oocytes were analyzed Main results and the role of chance: In fresh donor oocytes: 2PN rates significantly trended down from 96.3% to 90.7%, 89.2%, 66.7% from fine to central, uneven, dispersed granulations; overall pregnancy rates trended down from 48.8% to 29.0%, 19.0% and 6.4%, as did live birth rates (42.1%, 21.6%, 12.5%, 6.4%), from fine to uneven, central and dispersed granulations. Known-pregnancy and known-live-birth analyses showed similar findings. Thawed donor oocytes demonstrated similar trends, though with significantly worse outcomes than fresh oocytes. Peripheral granulation, unique to vitrification and thawing, always demonstrated the worst IVF outcomes. Interestingly, granulation patterns were mostly disassociated from morphologic embryo grades in fresh and thawed donor oocytes. Limitations, reasons for caution: As a retrospective cohort study, some cases had to be excluded for lack of information. The scoring system may have diluted the real contribution of an oocyte when two or more embryos were transferred. Wider implications of the findings: Ooplasm granulation patterns have predictive values for fertilization, pregnancy and live birth in IVF cycles, supporting integration of them into embryo selection, and suggesting that ooplasm granulation patterns reflect intrinsic features of oocytes that relate to oocyte quality, cytoplasmic maturity and developmental competence, but are largely independent of clinical co-variables. Trial registration number: NA